2015
DOI: 10.1111/jir.12184
|View full text |Cite
|
Sign up to set email alerts
|

Predictive validity of the HCR‐20 for inpatient aggression: the effect of intellectual disability on accuracy

Abstract: This study demonstrates that, after controlling for a range of potential covariates, the HCR-20 is a significant predictor of inpatient aggression in people with an ID and performs as well as for a comparison group of mentally disordered individuals without ID. The potency of HCR-20 subscales and items varied between the ID and comparison groups suggesting important target areas for improved prediction and risk management interventions in those with ID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“… 22 Similarly, a number of studies have reported elevated HCR-20 total and subscale scores among in-patients with intellectual disability, compared with those without. 5 , 6 , 17 , 23 Boer et al 24 outlined the principal items where people with intellectual disability may be likely to score higher on the HCR-20 than those without, such as relationship instability, employment problems and a lack of insight. However, regardless of the source of the problem relative to each item, each item is relevant to an accurate risk assessment of future violence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 Similarly, a number of studies have reported elevated HCR-20 total and subscale scores among in-patients with intellectual disability, compared with those without. 5 , 6 , 17 , 23 Boer et al 24 outlined the principal items where people with intellectual disability may be likely to score higher on the HCR-20 than those without, such as relationship instability, employment problems and a lack of insight. However, regardless of the source of the problem relative to each item, each item is relevant to an accurate risk assessment of future violence.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is important because of previous studies that reported that those with an intellectual disability within such services have higher rates of aggressive behaviour and higher scores on objective risk assessment tools. 5 , 6 Therefore, this study aimed to: (a) elucidate the characteristics and needs of patients with intellectual disability, who have been identified as ‘long stay’ within high and medium secure forensic psychiatric services, and (b) compare these with those who do not have a diagnosis of intellectual disability.…”
mentioning
confidence: 99%
“…Reports may also include near-incidents, where timely interventions prevented the incident from occurring. Incident reports of aggression in particular have shown to be related to clinical risk assessment for aggression (O'Shea et al 2015) and to be a helpful tool for care facilities to take measures towards guarding safety (Malda Castillo et al 2018).…”
mentioning
confidence: 99%
“…Self-harm incidents as a service-level outcome indicator were reported in only two studies. 59,62 Neither of these studies reported change over time in self-harm as a result of intervention at the service level.…”
Section: Reoffending/'offending-like' Behaviour/incidentsmentioning
confidence: 98%
“…Most commonly, services used the structured clinical judgement tool the Historical, Clinical Risk 20 . 23,33,34,43,53,54,58,59 Other studies reported on static risk assessment measures such as the Violence Risk Appraisal Guide (VRAG), 23,53,54 Risk Matrix 2000, 53 Offender Group Reconviction Scale 22 and Static-99, 53 although these would not have utility as outcome measures as they would not be expected to change. The vast majority of these studies reported only cross-sectional data and not within-patient change in such measures over time.…”
Section: Risk Assessmentmentioning
confidence: 99%